2020
DOI: 10.1002/jper.20-0104
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas gingivalis and Alzheimer disease: Recent findings and potential therapies

Abstract: Epidemiological studies have identified an association between periodontitis and Alzheimer disease (AD); however, the nature of this association has been unclear. Recent work suggests that brain colonization by the periodontal pathogen Porphyromonas gingivalis may link these two inflammatory and degenerative conditions. Evidence of P. gingivalis infiltration has been detected in autopsy specimens from the brains of people with AD and in cerebrospinal fluid of individuals diagnosed with AD. Gingipains, a class … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 34 publications
0
43
1
5
Order By: Relevance
“…It is worth noting that recent epidemiological studies have identified a strong association between the periodontal pathogen P. gingivalis and neurodegeneration. P. gingivalis has been detected in the brain autopsy and CSF of individuals diagnosed with AD ( Ryder, 2020 ). Another recent study demonstrated the presence of P. gingivalis -derived lipopolysaccharides in brain samples from AD patients ( Poole et al, 2013 ) and the presence of gingipains, a class of P. gingivalis proteases, in neurons, tau tangles, and Aβ of individuals with AD ( Dominy et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that recent epidemiological studies have identified a strong association between the periodontal pathogen P. gingivalis and neurodegeneration. P. gingivalis has been detected in the brain autopsy and CSF of individuals diagnosed with AD ( Ryder, 2020 ). Another recent study demonstrated the presence of P. gingivalis -derived lipopolysaccharides in brain samples from AD patients ( Poole et al, 2013 ) and the presence of gingipains, a class of P. gingivalis proteases, in neurons, tau tangles, and Aβ of individuals with AD ( Dominy et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…This exciting finding is potentially a major breakthrough for therapy based on low molecular weight small-molecules designed to block the toxic effects of the different types of gingipains secreted by P. gingivalis , which are currently in Phase III clinical trials. An aspect of the gingipains inhibitor COR388 based therapy is provided elsewhere [ 56 ].…”
Section: P Gingivalis Gingipains: the Most Critical Virulenmentioning
confidence: 99%
“…Dominy et al 8 suggested that “gingipains were neurotoxic in vivo and in vitro, exerting detrimental effects on tau” and thus exacerbating amyloid plaque formation, a key factor of Alzheimer disease development. While they reported exciting outcomes concerning the inhibition of gingipains 46 , a group of cysteine proteinases, controlling them in the brain could be a challenging endeavor and may require continuous treatments. Furthermore, the origin of gingipains in human brain needs further clarification.…”
Section: Discussionmentioning
confidence: 99%